2012
DOI: 10.4236/ijohns.2012.13016
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Nasal Septal Deformities in Kashmiri Population Attending a Tertiary Care Hospital

Abstract: The aim of this study is to determine the percentage of septal deformities in symptomatic patients in Kashmiri population, identified at otolaryngology clinic of a referral & a teaching tertiary care hospital SKIMS Medical College, Bemina, Srinagar, where 429 patients with nasal septal deviation were identified. All of the patients underwent nasal examination by anterior rhinoscope and nasal endoscopy. Pathological septal deformities were identified & grouped into five types by using SL classification. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
4
13
0
1
Order By: Relevance
“…This finding is similar to other studies conducted previously. 8,9 Mladina type 5 & 6 seems more common in nontraumatic group whereas type 1, 2 & 4 more common in traumatic group, which is significant ( Chi square test, p-value=0.02) as found in our study. Similar findings have been reported in other study also.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is similar to other studies conducted previously. 8,9 Mladina type 5 & 6 seems more common in nontraumatic group whereas type 1, 2 & 4 more common in traumatic group, which is significant ( Chi square test, p-value=0.02) as found in our study. Similar findings have been reported in other study also.…”
Section: Discussionsupporting
confidence: 82%
“…DNS was more prevalent in males than females as found in this study, which was in accordance to the observations made in other study. 8,10 DNS most commonly presents during second and third decades of life, as reported by several studies. 8,10 This finding is similar to that as in our study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast, a study by Rehman et al reported area 1 (19%) had the most frequent septal deviation followed by area 3 (10.48%) and area 4 (7%). 21 The deviation was also seen in combinations of areas 2, 3 and 4 (21.44%) followed by area 2 and 3 (20.04%).…”
Section: Discussionmentioning
confidence: 91%
“…Rehman ve ark. [8] yaptıkları çalışmada sağ tarafa deviasyonun daha sık görüldüğünü belirtmişlerdir. Çalışmamızda elde edilen farklı sonucun hasta nüfusunun sınırlı olmasından kaynaklanabileceği düşünüldü.…”
Section: Discussionunclassified